2015
DOI: 10.3109/02713683.2014.978478
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Prolongs Myofibroblast Accumulation in Corneal Stroma with Incisional Wound

Abstract: Purpose: The purpose of this study was to determine whether platelet-rich plasma (PRP) has an effect on corneal stromal cells in a rat model of wound healing following corneal incision. Materials and Methods: The effect of PRP on corneal wound healing in vivo was investigated in a corneal incision wound model in rats. 40 rats were wounded by deep corneal incision, and treated with either topically administered PRP (20 rats) or sodium chloride (20 rats). At 4 h and 1, 3, and 5 days after incision, a-smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In addition, corneas given topical PRP treatment exhibit higher proportions of α-SMA-positive myofibroblasts than control corneas. Notably, myofibroblast accumulation occurs due to modulation of the TGF-β pathway 64 . Therefore, in a matter of time PRP have accelerated fibrosis and neovascularization which is crucial in wound contraction and healing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, corneas given topical PRP treatment exhibit higher proportions of α-SMA-positive myofibroblasts than control corneas. Notably, myofibroblast accumulation occurs due to modulation of the TGF-β pathway 64 . Therefore, in a matter of time PRP have accelerated fibrosis and neovascularization which is crucial in wound contraction and healing.…”
Section: Discussionmentioning
confidence: 99%
“…PRP has an antiapoptotic effect on corneal stromal cells,5 and autologous platelets have been injected for the management of macular holes 6 7. Autologous platelets in the form of eye-drops or as a plasma gel have also been used in the management of several eye conditions depending on the desired effect and the purpose of the clinical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that topical PRP successfully treated dormant ulcers (hard-to-heal epithelial defects), dry eye syndromes, and ocular surface syndrome post Laser In Situ Keratomileusis (LASIK), as well as promoted surface reconstruction after corneal perforation associated with amnion transplantation (Alio et al, 2012;Alio et al, 2017;Rechichi et al, 2020). However, for stromal wound healing in a rat model, PRP treatment suppressed stromal cell apoptosis and increased myofibroblast generation by TGFβ/SMAD3 activation (Koulikovska et al, 2015). Hence, PRP seems to be effective in enhancing epithelial wound healing and promoting ocular surface regeneration in different pathological conditions.…”
Section: Smad Signaling Blockersmentioning
confidence: 99%